SISTEM INFORMASI PENERIMAAN SISWA BARU DI SEKOLAH DASAR NEGERI 3 RUKTI BASUKI BERBASIS WEBSITE - Pujianto; Mustaqim Sila, Edwar; Agus Priadi, Median (Universitas Muhammadiyah Metro, 2024)
New student admission activities are routine activities carried out by schools in every new school year. Elementary School 3 Rukti Basuki was established in 1978, and school conditions have not changed yearly, especially in the new student admission section. Students who want to register will be asked to come to school and then fill out a form, which will take more time and energy. This system is designed to process new student admissions, increase the efficiency of school administration, and provide convenience for prospective students and parents in accessing information without having to come. This system also allows prospective students and parents to complete application forms online and monitor and receive real-time notifications. This study is that the use of website-based technology in the new student admissions process at school can be an effective solution to reduce the administrative burden and improve the experience of prospective students and parents